Impact on soil microbial biota by pollutants from filling station - Acuña, Adrián Javier (2020)
Any chemical compound introduction in the soil, impact in bacterial community. This work aimed to observe the changes in the bacterial community of a soil that was contaminated with hydrocarbons (gasoline, diesel, oil and mixtures 1: 1 diesel-oil and 1: 1: 1 gasoline-diesel-oil). Microcosms were considered that were followed by mineralization, bacterial count, determination of TPH and acid extraction to monitor the bacterial community. There were disturbances in the composition of fatty acids of the bacterial community in all treatments. The addition of nutrients in the control system produces an increase in bacterial count and the system that best degraded was the system with diesel alone, the presence of hydrocarbons produced a grouping of samples with oil and mixtures in the PCA diagram.